Manufacturing method for RTB sintered magnets

JP7632118B2Active Publication Date: 2025-02-19PROTERIAL LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021106694
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-28
Publication Date
2025-02-19
Estimated Expiration
2041-06-28

AI Technical Summary

Benefits of technology

【0021】 本開示の実施形態によれば、ジェットミル粉砕を行うとき、粉砕効率を向上しつつ、酸素などの不純物の濃度上昇を抑制して、優れた磁気特性を有するR-T-B系焼結磁石を製造することが可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632118000006
    Figure 0007632118000006
  • Figure 0007632118000001
    Figure 0007632118000001
  • Figure 0007632118000002
    Figure 0007632118000002
Patent Text Reader

Abstract

To suppress the deterioration of magnet properties due to nitridation and oxidation, which tend to occur when the powder particle size is small.SOLUTION: A manufacturing method of an R-T-B based sintered magnet according to the present disclosure is a manufacturing method of an R-T-B based sintered magnet (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one transition metal and must contain Fe), and includes the steps of preparing a coarsely pulverized powder of an R-T-B based sintered magnet alloy, supplying a coarsely pulverized powder to a jet mill device in which a pulverizing chamber is filled with an inert gas to pulverize the coarsely pulverized powder to obtain a fine powder, and producing a sintered body of the fine powder, and a phosphite having a melting point of 20°C or higher and 100°C or lower is added to the coarsely pulverized powder.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a method for producing an RTB based sintered magnet. [Background technology]

[0002] RTB sintered magnets (R is a rare earth element and must contain at least one selected from the group consisting of Nd, Pr and Ce, T is at least one transition metal and must contain Fe, and B is boron) are represented by the formula RFe 14 It is composed of a main phase of a compound having a B-type crystal structure, a grain boundary phase located at the grain boundaries of this main phase, and a compound phase formed by the influence of trace additive elements and impurities. RTB-based sintered magnets have a high residual magnetic flux density B r (Hereinafter, simply "B r ") and high coercive force H cJ (Hereafter, simply "H cJ ") and is known as the highest performance magnet among permanent magnets.

[0003] For this reason, RTB sintered magnets are used in a variety of motors in the automotive sector, including electric vehicles (EVs, HVs, PHVs), renewable energy sectors such as wind power generation, home appliances, and industrial sectors. RTB sintered magnets are an essential material for making these motors smaller, lighter, more efficient, and more energy-efficient (improved energy efficiency). RTB sintered magnets are also used in the drive motors of electric vehicles, and the replacement of internal combustion engine vehicles with electric vehicles contributes to preventing global warming by reducing greenhouse gases such as carbon dioxide (reducing fuel and exhaust gases). In this way, RTB sintered magnets are making a significant contribution to the realization of a green energy society.

[0004] Such an RTB sintered magnet is manufactured through steps such as preparing an alloy powder, press-molding the alloy powder to produce a powder compact, and sintering the powder compact. The alloy powder is manufactured, for example, by the following method.

[0005] First, an alloy is produced from molten metals of various raw materials by an ingot method, strip casting method, or the like. The obtained alloy is subjected to a pulverization process to obtain an alloy powder having a predetermined particle size distribution. This pulverization process usually includes a coarse pulverization process and a fine pulverization process, the former of which is carried out by utilizing, for example, the hydrogen embrittlement phenomenon, and the latter of which is carried out by using, for example, an airflow pulverizer (jet mill).

[0006] There is a demand for RTB sintered magnets with even higher performance and lower costs. Methods for improving performance include, for example, making the structure finer and reducing the amount of oxygen contained, while methods for reducing costs include, for example, improving the efficiency of pulverization. Patent Document 1 discloses a method for improving pulverization efficiency, in which jet mill pulverization is performed using a humidified inert gas stream with a dew point of -20°C to 0°C. A similar method is also described in Patent Document 2. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-148317 [Patent Document 2] Japanese Patent Application Publication No. 6-140220 Summary of the Invention [Problem to be solved by the invention]

[0008] When producing an RTB sintered magnet with a reduced oxygen content, for example 4000 ppm or less, high-purity nitrogen gas is used as the inert gas to prevent oxidation of the powder particles during the crushing process.

[0009] According to the study of the present inventors, even when jet mill grinding is performed using an inert gas such as high-purity nitrogen gas, it has been found that there are cases where a reaction with impurities in the gas occurs, making it impossible to achieve the high performance that should be achieved by reducing oxygen. Furthermore, when trying to improve performance by making the powder finer, the grinding efficiency decreases. According to the methods disclosed in Patent Documents 1 and 2, the grinding efficiency can be improved, but the oxygen content exceeds 4500 ppm in order to suppress reactivity, and therefore this cannot be applied to the technology of improving performance by reducing oxygen. The embodiment of the present disclosure provides a method for producing an RTB-based sintered magnet that can solve such problems. [Means for solving the problem]

[0010] In a non-limiting exemplary embodiment, the method for producing an RTB based sintered magnet according to the present disclosure is a method for producing an RTB based sintered magnet (R is a rare earth element and necessarily includes at least one selected from the group consisting of Nd, Pr, and Ce, and T is at least one transition metal and necessarily includes Fe), and includes the steps of preparing a coarsely pulverized powder of an alloy for the RTB based sintered magnet, supplying the coarsely pulverized powder to a jet mill device whose pulverizing chamber is filled with an inert gas to pulverize the coarsely pulverized powder to obtain a fine powder, and producing a sintered body of the fine powder. A phosphite ester having a melting point of 20°C or more and 100°C or less is added to the coarsely pulverized powder.

[0011] In one embodiment, the phosphite ester is a compound represented by the following general formula (1): [ka]

[0012] R 1 and R 2 are aliphatic hydrocarbon groups having 2 to 34 carbon atoms, and R 1 The number of carbon atoms and R 2 The total number of carbon atoms in the alkyl group is 24 or more and 36 or less.

[0013] In one embodiment, R1 and R 2 are aliphatic hydrocarbon groups having 12 to 18 carbon atoms.

[0014] In one embodiment, the phosphite is R 1 and R 2 are respectively, C 12 H 25 Dilauryl hydrogen phosphite, which is R 1 and R 2 are respectively, C 18 H 35 The compound must contain at least one of the dioleylhydrogen phosphites:

[0015] In one embodiment, the amount of the phosphite added to the coarsely pulverized powder is 0.02% or more and 0.2% or less in terms of mass ratio.

[0016] In one embodiment, the RTB based sintered magnet has an oxygen content of 400 ppm or more and 4000 ppm or less.

[0017] In one embodiment, the RTB based sintered magnet has an R content of 31 mass % or less.

[0018] In one embodiment, the inert gas is nitrogen gas.

[0019] In one embodiment, the method includes a diffusion step of diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside.

[0020] In one embodiment, the fine powder in the step of obtaining the fine powder has an average particle size of 2.0 μm or more and 3.5 μm or less. Effect of the Invention

[0021] According to the embodiments of the present disclosure, when performing jet mill pulverization, it is possible to produce an RTB based sintered magnet with excellent magnetic properties by improving the pulverization efficiency while suppressing an increase in the concentration of impurities such as oxygen. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a diagram showing a schematic configuration example of a crushing system 1000 for an RTB sintered magnet alloy according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] As a result of the inventor's investigation, it was found that when manufacturing RTB sintered magnets with reduced oxygen content, in order to obtain fine powder with an average particle size of 3.5 μm or less in the pulverization process, in addition to the reduction in pulverization efficiency, the powder particles are deteriorated (nitrided, oxidized, carbonized) by the inert gas (mainly nitrogen gas) used in pulverization and the impurities in the gas, and the desired improvement in magnetic properties cannot be obtained. As a result of further investigation, the inventor found that by adding a phosphite ester with a melting point of 20°C to 100°C to the coarsely pulverized powder and then pulverizing it, it is possible to significantly improve the pulverization efficiency while suppressing the nitridation and oxidation of the powder particles during the pulverization process. This is thought to be because the formation of a thin film of the phosphite ester on the surface of the powder particles during the pulverization process suppresses the reaction of the powder particles with the inert gas (e.g., nitrogen gas) and the impurities in the gas (moisture, carbon dioxide, etc.), and also suppresses the aggregation of the powder particles during pulverization, so that the energy of the pulverization gas is efficiently used for pulverization without being used to break down the aggregates. It has been known that the grinding efficiency decreases when powder particles are reduced in size in the grinding process, and that this decrease can be improved by using a humidified inert gas flow (for example, Patent Document 1 and Patent Document 2). However, it goes without saying that grinding using a humidified inert gas flow can oxidize the powder particles and cause deterioration of their magnetic properties. As a result of the inventor's investigation, it was found that the use of a phosphite ester having a melting point of 20°C or higher and 100°C or lower can significantly improve the grinding efficiency while reducing the deterioration (nitridation and oxidation) of powder particles caused by the above-mentioned inert gas.

[0024] Phosphites with melting points between 20°C and 100°C may be in a liquid or partially molten state during the grinding process. For example, C 12 H 25 Dilauryl hydrogen phosphite and C 18 H 35Phosphites such as dioleyl hydrogen phosphite having an aliphatic hydrocarbon group have a melting point close to room temperature. During the pulverization process, at the moment of pulverization, they are liquefied by the impact energy and are considered to be solidified immediately after being cooled by the pulverization gas. By using an oil agent having such a melting point, it is considered that the surface such as the fracture surface of the powder particles formed by pulverization is easily covered with phosphite.

[0025] Furthermore, phosphites having a melting point of 20 °C or higher and 100 °C or lower are less volatile than oil agents having a melting point of less than 20 °C. When using an oil agent that is easily volatile, the components volatilized from the oil agent become gas and are mixed into the pulverization gas. Therefore, when circulating the pulverization gas in the pulverization system, it becomes difficult to accurately grasp and control the component amount of the oil agent contained in the pulverization gas. Therefore, the smaller the evaporation amount of the oil agent, the more preferable it is. From this point of view, phosphites having a melting point of 20 °C or higher and 100 °C or lower have high practicality.

[0026] Note that usually, the process in which the oxygen amount of the R-T-B sintered magnet increases in the process after pulverization is mainly the process of forming and sintering the fine powder to produce a sintered body. However, the increase in the oxygen content of the R-T-B sintered magnet by these processes is small (for example, 50 ppm or more and 300 ppm or less).

[0027] <Manufacturing method of R-T-B sintered magnet> Hereinafter, embodiments of the manufacturing method of the R-T-B sintered magnet according to the present disclosure will be described.

[0028] In the R-T-B sintered magnet manufactured by the manufacturing method of this embodiment, R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce. Further, T is at least one of transition metals and necessarily contains Fe.

[0029] The manufacturing method of this R-T-B sintered magnet is (1) A step of preparing a coarse pulverized powder of an alloy for an R-T-B sintered magnet, and (2) A step of supplying the coarsely pulverized powder to a jet mill device filled with an inert gas in a pulverization chamber to pulverize the coarsely pulverized powder and obtain a fine powder; (3) A step of producing a sintered body of the fine powder; The method includes the above steps, and a phosphite having a melting point of 20°C or higher and 100°C or lower is added to the coarsely pulverized powder in step (2).

[0030] <R-T-B sintered magnet> In the R-T-B sintered magnet of the present disclosure, the oxygen content is 400 ppm or more and 4000 ppm or less by mass ratio. By setting the oxygen content to 400 ppm or more and 4000 ppm or less, a decrease in magnetic properties can be suppressed. In order to obtain higher magnetic properties, the oxygen content of the R-T-B sintered magnet is preferably 400 ppm or more and 2500 ppm or less, and more preferably 400 ppm or more and 1500 ppm or less.

[0031] The following shows the composition of a preferred R-T-B sintered magnet.

[0032] R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr, and Ce. Preferably, a combination of rare earth elements represented by Nd-Dy, Nd-Tb, Nd-Dy-Tb, Nd-Pr-Dy, Nd-Pr-Tb, Nd-Pr-Dy-Tb is used.

[0033] Among R, Dy and Tb are particularly H cJIt is effective in improving the above-mentioned elements. In addition to the above elements, other rare earth elements such as La may be contained, and misch metal or didymium may also be used. Furthermore, R does not have to be a pure element, and may contain impurities that are unavoidable in the manufacturing process within the range of industrial availability. The content is, for example, 27% by mass to 35% by mass. The R content of the RTB sintered magnet is preferably 31% by mass or less (27% by mass to 31% by mass), more preferably 29% by mass to 31% by mass. By making the R content of the RTB sintered magnet 31% by mass or less and the oxygen content 400 ppm to 4000 pp (preferably 400 ppm to 2500 ppm, and even more preferably 400 ppm to 1500 ppm), the generation of oxidized R is reduced. Therefore, higher magnetic properties can be obtained.

[0034] T contains iron (including the case where T is substantially composed of iron), and up to 50% by mass of iron may be replaced with cobalt (Co) (including the case where T is substantially composed of iron and cobalt). Co is effective for improving temperature characteristics and corrosion resistance, and the alloy powder may contain up to 10% by mass of Co. The content of T may be the remainder of R and B, or R, B, and M described below.

[0035] The content of B may be a known content, and for example, a preferred range is 0.9% by mass to 1.2% by mass. If it is less than 0.9% by mass, high H cJ If it exceeds 1.2 mass%, B may not be obtained. r In addition, a part of B can be replaced with C (carbon).

[0036] In addition to the above elements, H cJ In order to improve the properties, an M element can be added. The M element is one or more selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Ni, Cu, Zn, Ga, Zr, Nb, Mo, In, Sn, Hf, Ta and W. The amount of M element added is preferably 5.0 mass% or less. If it exceeds 5.0 mass%, Br may decrease. Inevitable impurities are also acceptable.

[0037] The N (nitrogen) content in the RTB sintered magnet is preferably 50 ppm or more and 900 ppm or less. By pulverizing the magnet so that the N (nitrogen) content is 50 ppm or more and 900 ppm or less, it is possible to improve pulverizability while suppressing the deterioration of magnetic properties due to nitriding. The nitrogen content is more preferably 50 ppm or more and 800 ppm or less, and most preferably 100 ppm or more and 800 ppm or less. This is because it is possible to further improve pulverizability while suppressing the deterioration of magnetic properties due to nitriding. Furthermore, the C (carbon) content in the RTB sintered magnet is preferably 50 ppm or more and 1300 ppm or less.

[0038] <(1) Example of a process for preparing coarsely pulverized powder of alloy for RTB sintered magnets> In this embodiment, the step of preparing a coarsely pulverized powder of an alloy for an RTB based sintered magnet may include a step of preparing an alloy for an RTB based sintered magnet and a step of coarsely pulverizing this alloy by, for example, a hydrogen pulverization method.

[0039] The following is an example of a method for producing an alloy for an RTB based sintered magnet.

[0040] First, an alloy ingot can be obtained by ingot casting, in which a metal or alloy previously adjusted to have the above-mentioned composition is melted and poured into a mold. Alternatively, alloy flakes can be produced by a quenching method, typically a strip casting method or a centrifugal casting method, in which the molten metal is brought into contact with a single roll, a twin roll, a rotating disk, or a rotating cylindrical mold, and quenched to produce a solidified alloy thinner than the alloy produced by the ingot method.

[0041] In the embodiment of the present disclosure, materials produced by either the ingot method or the quenching method can be used, but it is preferable to produce the alloy by a quenching method such as a strip casting method. The thickness of the quenched alloy produced by the quenching method is usually in the range of 0.03 mm to 1 mm, and it is in a flake shape. The alloy melt starts to solidify from the surface (roll contact surface) that contacts the cooling roll, and crystals grow columnarly from the roll contact surface in the thickness direction. The quenched alloy is cooled in a short time compared to the alloy (ingot alloy) produced by the conventional ingot casting method (mold casting method), so the structure is finer and the crystal grain size is smaller. In addition, the area of ​​the grain boundary is large. Since the R-rich phase spreads widely within the grain boundary, the quenching method has excellent dispersibility of the R-rich phase. Therefore, it is easy to break at the grain boundary by the hydrogen pulverization method. By hydrogen pulverizing the quenched alloy, the size (average grain size) of the hydrogen pulverized powder (coarsely pulverized powder) can be, for example, 1.0 mm or less, preferably 10 μm to 500 μm.

[0042] <(2) Example of process for obtaining fine powder> In the process of obtaining fine powder in this embodiment, the coarsely pulverized powder is supplied to a jet mill device whose pulverization chamber is filled with an inert gas, and the coarsely pulverized powder is pulverized to obtain fine powder. In this process, for example, fine powder having an average particle size of 2.0 μm or more and 3.5 μm or less can be obtained. The process of obtaining such fine powder can be carried out, for example, by using a pulverization system described later.

[0043] In this embodiment, a phosphite having a melting point of 20° C. or more and 100° C. or less is added to the coarsely pulverized powder and then pulverized. In a preferred embodiment, the phosphite is a compound represented by the following general formula (1). [ka]

[0044] Here, R 1 and R 2 R is an aliphatic hydrocarbon group having 2 to 34 carbon atoms. 1 The number of carbon atoms and R 2and the total number of carbon atoms is preferably 24 or more and 36 or less. 1 and R 2 and R are each preferably an aliphatic hydrocarbon group having 12 to 18 carbon atoms. 1 and R 2 are respectively, C 12 H 25 Dilauryl hydrogen phosphite and C 18 H 35 This includes dioleyl hydrogen phosphite.

[0045] By adding such a phosphorous acid ester having a melting point of 20°C or more and 100°C or less to the coarsely pulverized powder and then pulverizing the powder, it is possible to improve the pulverization efficiency and suppress the volatilization of the components into the pulverization gas. If the melting point is less than 20°C, the powder will exist as a liquid in the pulverizer, and there is a high possibility of volatilization, and there is a concern that the powder will become clogged due to the inside of the piping becoming wet, and if the melting point is more than 100°C, it cannot be melted in a hot water bath, making it difficult to handle industrially. The preferred range of the melting point is 20°C or more and 90°C or less.

[0046] The amount of phosphite added to the coarsely pulverized powder is, for example, 0.02% or more and 0.2% or less by mass. This means that 0.02% to 0.2% by mass of phosphite is added to 100% by mass of the coarsely pulverized powder. If the amount added is less than 0.02% by mass, the amount is too small and the improvement of the pulverization efficiency is insufficient, and if it exceeds 0.2%, the carbon content of the sintered body is excessively high and the magnetic properties may deteriorate. According to the examples described later, when an RTB sintered magnet is produced from a powder obtained by adding 0.02% or more and 0.2% or less by mass of dilauryl hydrogen phosphite to the coarsely pulverized powder and finely pulverizing it, the increase in oxygen, nitrogen, and carbon in the RTB sintered magnet due to the addition of this oil agent was -500ppm, +100ppm, and -100ppm, respectively, compared to the case of humidified pulverization.

[0047] <Crushing system> A pulverization system that can be used in the manufacturing method of the RTB sintered magnet according to the present disclosure will be described with reference to Fig. 1. Fig. 1 is a diagram showing a schematic configuration example of a pulverization system 1000 in this embodiment. In this example, the RTB sintered magnet alloy pulverization system 1000 includes a jet mill device 100, a cyclone collection device 200, and a bag filter device 300.

[0048] The jet mill device 100 receives the material to be pulverized from a raw material tank (not shown) via a raw material input pipe 34. The material to be pulverized is, for example, a coarsely pulverized powder of an alloy for an RTB sintered magnet having an average particle size of 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (compliant with JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%. More specifically, the average particle size (d50) in the embodiments of the present disclosure is measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec. Dispersion pressure: 4bar Measurement range: R2 Calculation mode: HRLD This indicates the d50 measured under the conditions above.

[0049] The raw material input pipe 34 is provided with multiple valves, and the internal pressure of the jet mill device 100 is appropriately maintained by opening and closing the valves. The material to be pulverized introduced into the jet mill device 100 is finely pulverized by collisions between the materials to be pulverized due to high-speed injection of inert gas from the nozzle pipe 36 and collisions with collision plates installed to efficiently advance the pulverization.

[0050] In general, alloy powder for RTB sintered magnets is active and easily oxidized. For this reason, it is preferable to use a dry (high purity) inert gas such as nitrogen, argon, or helium with a dew point of -60°C or less as the gas used in the jet mill device 100 in order to avoid the risk of heat generation and fire and to reduce the oxygen content as an impurity to improve the performance of the magnet. However, the addition of a phosphite ester with a melting point of 20°C to 100°C reduces the reactivity of the powder particles, so the grinding gas does not necessarily need to be in a dry state with a dew point of -60°C or less.

[0051] The powder particles (fine powder) finely pulverized inside the jet mill device 100 are carried by the ascending air current and guided from the upper outlet to the inlet pipe 20 of the cyclone collector 200. Coarse particles that are not sufficiently pulverized are separated by a classification rotor installed to classify coarse particles having a median diameter (d50) or more. Thus, the coarse particles having a median diameter (d50) or more remain inside the jet mill device 100 and are further subjected to a crushing process by collision. Such classification of coarse particles may be performed using a classification rotor or centrifugal separation by a swirling flow. Thus, the material to be crushed (coarsely crushed powder) fed into the jet mill device 100 is crushed into fine powder having a particle size distribution, for example, with an average particle size (median diameter: d50) of 2.0 μm or more and 4.5 μm or less, and then moved to the cyclone collector 200.

[0052] The cyclone collector 200 is used to separate the powder from the airflow carrying the powder. Specifically, coarsely pulverized powder of an alloy for RTB-based sintered magnets is pulverized in a jet mill at a front stage, and the fine powder generated by the pulverization is supplied to the cyclone collector 200 through an inlet pipe 20 together with the gas used for the pulverization. A mixture of an inert gas (pulverization gas) and the pulverized fine powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate the pulverization gas and the fine powder. The fine powder separated from the pulverization gas is collected by a powder collector 50 through an outlet 40. The pulverization gas is supplied to a bag filter device 300 through an outlet pipe 30. In the bag filter device 300, very small particles are collected, and clean gas is discharged to the outside through an exhaust port 32. For such solid-gas separation, it is possible to use a bag filter instead of the cyclone collector 200, but this would have a large impact on the environment and safety, such as the dispersion of fine powder into the air due to damage to the filter. Fine particles may be further separated from the gas separated by the cyclone collector by using a bag filter in combination.

[0053] A characteristic feature of the present disclosure is that a phosphite ester having a melting point of 20° C. or more and 100° C. or less is added to the coarsely pulverized powder and then pulverized. This makes it possible to suppress the deterioration of the powder particles (both nitridation and oxidation) caused by pulverization and obtain high magnetic properties.

[0054] The dew point in the grinding chamber and the amount of coarsely ground powder supplied to the jet mill depend on the grinding time and the size of the jet mill, but in a preferred embodiment, the inert gas is adjusted so that the dew point during grinding is between -80°C and -60°C. In a preferred embodiment, the rate at which the coarsely ground powder is supplied to the jet mill is, for example, when the gas flow rate is 1 Nm 3 For a jet mill with a capacity of 10000 / min, the capacity is between 3 kg / hr and 12 kg / hr.

[0055] Examples of inert gases are nitrogen, argon, and helium. Among them, nitrogen is the most preferable because it is available at a low cost as a high-purity gas. Therefore, in a preferred embodiment, the inert gas is nitrogen gas. However, as a result of the study by the present inventor, it was found that when jet mill pulverization is performed using an inert gas made of nitrogen, when the average particle size of the resulting fine powder is 4.5 μm or less, the magnetic properties begin to deteriorate due to nitriding. In particular, when the average particle size is 3.5 μm or less, the deterioration of the magnetic properties due to nitriding may become significant. However, according to the embodiment of the present disclosure, since a phosphorous ester having a melting point of 20° C. or more and 100° C. or less is added to the coarsely pulverized powder and pulverized, it is possible to suppress both nitriding and oxidation even if nitrogen gas is used as the inert gas.

[0056] The increase in oxygen content of the RTB sintered magnet due to the process after fine pulverization (mainly the process of producing a sintered body from the fine powder) is preferably 50 ppm to 300 ppm, more preferably 50 ppm to 200 ppm. To achieve this, as described below, wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere is performed, and the resulting molded body is sintered. The average particle size of the fine powder in the process of obtaining the fine powder is more preferably 2.0 μm to 3.5 μm. By reducing the average particle size, it is possible to improve the magnetic properties.

[0057] <(3) Example of a process for producing a sintered body of fine powder> In a preferred embodiment, the step of producing a sintered body of fine powder includes a step of producing a powder compact from the fine powder by pressing in a magnetic field, and a step of sintering the powder compact. In the case of pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or wet pressing from the viewpoint of suppressing oxidation. In particular, in the case of wet pressing, the surface of the particles constituting the powder compact is covered with a dispersant such as an oil agent, and contact with oxygen or water vapor in the air is suppressed. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing step.

[0058] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing fine powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing device and press-molded in a magnetic field.

[0059] ·Dispersion medium The dispersion medium is a liquid in which the alloy powder can be dispersed to obtain a slurry.

[0060] A preferred dispersion medium used in the present disclosure may be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increased viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet compaction in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. If the fractional point of the mineral oil or synthetic oil exceeds 400°C, it may be difficult to remove the oil after obtaining a compact, and the amount of residual carbon in the sintered body may increase, resulting in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.

[0061] - Preparation of slurry The obtained alloy powder is mixed with a dispersion medium to obtain a slurry.

[0062] The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3This is because, at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and then the alloy powder and the dispersion medium may be weighed and mixed in a predetermined amount. In addition, when obtaining alloy powder by dry-pulverizing the coarsely pulverized powder with a jet mill or the like, a container containing the dispersion medium may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly collected in the dispersion medium in the container to obtain a slurry. In this case, it is preferable that the atmosphere inside the container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain a slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the dispersion medium using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the dispersion medium.

[0063] The slurry thus obtained is molded in a known wet press to obtain a molded body having a desired size and shape, which is then sintered to obtain a sintered body.

[0064] Sintering process Next, the compact is sintered to obtain a rare earth sintered magnet body (sintered body).

[0065] The compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4 The sintering is carried out at a pressure of 1000 to 1150 Torr or less and at a temperature of 1000 to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions for the heat treatment, such as the heat treatment temperature and heat treatment time, can be adopted. The rare earth sintered magnet body thus obtained is subjected to a grinding / polishing process, a surface treatment process, and a magnetization process as necessary to complete the final rare earth sintered magnet.

[0066] In a preferred embodiment, the method for producing an RTB based sintered magnet of the present disclosure includes a diffusion step of diffusing a heavy rare earth element RH (RH is at least one of Tb, Dy, and Ho) from the surface of a sintered body to the inside. Diffusion of the heavy rare earth element RH from the surface to the inside of a sintered body can efficiently increase the coercive force. As shown in the examples described later, when a diffusion step is performed on a sintered body that has been pulverized after adding a phosphite having a melting point of 20°C or more and 100°C or less to a coarsely pulverized powder, a higher H cJ The method for the diffusion step is not particularly limited, and any known method can be used. EXAMPLES

[0067] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.

[0068] Example 1 Alloys for RTB sintered magnets were prepared by strip casting so as to have the compositions of RTB sintered magnets shown in Samples No. 1 to 5 in Table 1 (excluding O, C, and N). Each of the obtained alloys was coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. In addition, zinc stearate was prepared as a comparative example to be added to the coarsely pulverized powder. In addition, as an example of the present invention, zinc stearate, a phosphite ester having a melting point of 20°C to 100°C and R 1 and R 2 are respectively, C 12 H 25 Dilauryl hydrogen phosphite, which is R 1 and R 2 are respectively, C 18 H 35 A dioleylhydrogen phosphite having the formula:

[0069] The coarsely pulverized powder was fed into the jet mill device 100 shown in FIG. 1 and pulverized to obtain a fine powder. The pulverization conditions are shown in Table 2. No. 3 in Table 2 was 1 Nm 3The powder was humidified and pulverized by adding 0.05 g of water per 1000 g of water to the inert gas, and the amount of zinc stearate added to the coarsely pulverized powder was 0.04% by mass. Nos. 1, 2, 4, and 5 are also described in the same manner (therefore, all powders except No. 3 were humidified and pulverized). In this embodiment, nitrogen gas was used as the inert gas. The average particle size of the obtained fine powder is shown in Table 2. In this disclosure, the average particle size means the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%. The average particle size (d50) was measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, measurement range: R2, and calculation mode: HRLD. The fine powder was immersed in mineral oil in a nitrogen atmosphere to prepare a slurry. The slurry concentration was 85% by mass. The obtained slurry was molded (wet molding) in a magnetic field to obtain a molded body. The molding device used was a so-called rectangular magnetic field molding device (horizontal magnetic field molding device), in which the magnetic field application direction and the pressure direction are perpendicular to each other. The obtained green body was sintered in a vacuum at 1,020°C (a temperature selected so that sufficient densification by sintering occurs) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3 The results were as above. The sintered body was then subjected to a heat treatment in which it was held at 800°C for 2 hours, cooled to room temperature, and then held at 500°C for 2 hours and cooled to room temperature to obtain an RTB sintered magnet). The components of the obtained sintered magnet were determined. The contents of Nd, Pr, B, Co, Al, Cu, and Ga were measured by ICP atomic emission spectrometry. Furthermore, O (oxygen content) was measured by gas fusion-infrared absorption method, N (nitrogen content) by gas fusion-thermal conduction method, and C (carbon content) by combustion-infrared absorption method, all using a gas analyzer. The results are shown in Table 1. The sintered magnet was machined to prepare samples measuring 7 mm in length, 7 mm in width, and 7 mm in thickness, and the B content of each sample was measured using a BH tracer. r and H cJ The measurement results are shown in Table 2.

[0070] [Table 1]

[0071] [Table 2]

[0072] As shown in Table 2, Nos. 4 and 5, which are examples of the present invention, all have higher grinding efficiency than the comparative examples (Nos. 1 to 3). In addition, No. 2, which has an increased amount of zinc stearate added from No. 1, and No. 3, which was subjected to humidified grinding, all have improved grinding efficiency compared to No. 1, but the grinding efficiency is lower than that of the examples of the present invention. cJ is declining. [Industrial Applicability]

[0073] The method for producing an RTB based sintered magnet according to the present disclosure can be used to produce permanent magnets for a wide variety of applications, such as voice coil motors (VCMs) for hard disk drives, motors for electric vehicles (EVs, HVs, PHVs), motors for industrial equipment, and other motors, as well as home appliances. [Explanation of symbols]

[0074] 100···Jet mill equipment, 200···Cyclone collection equipment, 300···Bag filter equipment

Claims

1. A method for producing an R-T-B based sintered magnet (R is a rare earth element and necessarily contains at least one selected from the group consisting of Nd, Pr and Ce, and T is at least one transition metal and necessarily contains Fe), comprising the steps of: preparing a coarsely pulverized powder of an alloy for an R-T-B based sintered magnet; A step of supplying the coarsely pulverized powder to a jet mill device having a pulverization chamber filled with an inert gas to pulverize the coarsely pulverized powder to obtain a fine powder; preparing a sintered body of the fine powder; Including, In the method for producing an RTB based sintered magnet, a phosphite having a melting point of 20° C. or higher and 100° C. or lower is added to the coarsely pulverized powder.

2. The phosphite ester is a compound represented by the following general formula (1): 【Chemistry 1】 R 1 and R 2 are each an aliphatic hydrocarbon group having 2 to 34 carbon atoms, R 1 The number of carbon atoms and R 2 2. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the total number of carbon atoms in the

3. R 1 and R 2 and each are an aliphatic hydrocarbon group having 12 or more and 18 or less carbon atoms.

4. The phosphite ester is R 1 and R 2 are respectively, C 12 H 25 and dilauryl hydrogen phosphite represented by R 1 and R 2 are respectively, C 18 H 35 The method for producing a sintered R-T-B magnet according to claim 3, wherein the method necessarily contains at least one of dioleylhydrogen phosphite represented by the formula (1) and (2).

5. 5. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the amount of the phosphite added to the coarsely pulverized powder is equal to or greater than 0.02% and equal to or less than 0.2% by mass.

6. The method for producing a sintered RTB based magnet according to any one of claims 1 to 5, wherein the oxygen content of the sintered RTB based magnet is 400 ppm or more and 4000 ppm or less.

7. The method for producing a sintered R-T-B based magnet according to any one of claims 1 to 6, wherein the R content of the sintered R-T-B based magnet is 31 mass % or less.

8. The method for producing a sintered RTB system magnet according to claim 1, wherein the inert gas is nitrogen gas.

9. 9. The method for producing an R-T-B based sintered magnet according to claim 1, further comprising a diffusion step of diffusing a heavy rare earth element RH (RH being at least one of Tb, Dy, and Ho) from the surface of the sintered body to the inside.

10. 10. The method for producing a sintered RTB based magnet according to claim 1, wherein the fine powder in the step of obtaining the fine powder has an average particle size of 2.0 μm or more and 3.5 μm or less.

Citation Information

Patent Citations

  • Manufacture of raw material powder for rare-earth magnet

    JP1994140220A

  • Production of rare earth magnet

    JP1996148317A

  • Bonded magnet composition and bonded magnet using the same

    JP2009283596A

  • Method and equipment for producing powder of neodymium-iron-boron rare-earth permanent magnetic alloy

    JP2015214745A

  • Method for increasing coercive force of magnets

    JP2016122863A